FTIR spectroscopy combined with multivariate calibration for analysis of cod liver oil in binary mixture with corn oil - Abdul Rohman,; Che Man, Yaakob; Ismail, Amin; Hashim, Puziah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
FTIR spectroscopy in combination with multivariate calibrations, i.e. partial least square (PLS) and principle component regression (PCR) was developed for quantitative analysis of cod liver oil (CLO) in binary mixture with corn oil (CO). The spectra of CLO, CO and their blends with certain concentrations were scanned using horizontal attenuated total reflectance (HATR) accessory at mid infrared (MIR) region of 4,000 – 650 cm-1. The optimal spectral treatments selected for calibration models were based on its ability to provide the highest values of coefficient of determination (R2 ) and the lowest values of root mean error of calibration (RMSEC). PLS was slightly well suited for quantitative analysis of CLO compared to PCR. FTIR spectroscopy in combination with multivariate calibration offers rapid, no excessive chemical reagent, and easy in operational to be applied for determination of CLO in binary mixture with other oils.